Pengaruh Kombinasi Briket Batubara Antrasit Dan Serbuk Arang Tempurung Kelapa Terhadap Kuat Tekan Dengan Variasi Parameter Proses - Habib Al Aziz, Putra; Wahyudie, Ilham Ary; Yuliyanto, Yuliyanto (Jurnal Inovasi Teknologi Terapan, 2025)
Coal is one of Indonesia's most abundant energy and mineral resources in the mining sector, remaining a primary energy source globally. This study aims to analyze the effect of combining anthracite coal and coconut shell charcoal powder on the compressive strength of briquettes with variations in process parameters, including temperature, heating time, and water:molasses ratio as a binder. Briquettes were produced using a composition of 90% anthracite coal and 10% coconut shell charcoal powder, with molasses binders in ratios of 4:1 and 4:3. Compressive strength tests were conducted at temperatures of 100°C and 120°C with heating times of 60 and 90 minutes. The results indicate that the optimal combination to achieve the highest compressive strength was at a temperature of 120°C, a heating time of 90 minutes, and a water:molasses ratio of 4:3, yielding a compressive strength of 506.3 kPa (5.166 kg/cm²). Increasing temperature and a higher molasses ratio significantly improved the mechanical strength of the briquettes, while prolonged heating at lower temperatures tended to reduce compressive strength due to binder degradation. Therefore, further research is needed to optimize process parameters to meet national standards and enhance briquette durability.